Cirsium setidens Nakai extract and pectolinarin as active compounds promote innate immunity in RAW 264.7 cells and splenocytes - Se Jeong Kim; San Kim; Ardina Nur Fauziah; Jeong Min Park; Jung A Ryu; Sung Ran Yoon; Chae Min Han; Sung Keun Jung (Applied Food Research)
This study aimed to investigate the enhancement effect of Cirsium setidens Nakai water extract (CNE) on innate immunity. We found CNE to enhance nitric oxide and reactive oxygen species production in RAW 264.7 cells without exhibiting cytotoxicity. Additionally, CNE increased inducible nitric oxide synthase and cyclooxygenase-2 expression. It also dose-dependently increased the protein expression of interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) genes in RAW 264.7 cells. CNE upregulated the activation of the NF-κB and MAPK pathways in RAW 264.7 cells. Analysis of cytosolic and nuclear protein fractions, along with immunofluorescence analysis, revealed that CNE promoted the nuclear translocation of p65 and c-Jun in RAW 264.7 cells. In concanavalin A (Con A)-stimulated splenocytes, CNE alleviated the dexamethasone (DEX)-induced reduction of splenocyte proliferation. It also suppressed the DEX-induced diminution of IL-1β and IL-6 production in the cultured supernatant of Con A-stimulated splenocytes. Furthermore, CNE enhanced NO secretion in peritoneal macrophages. Ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry identified pectolinarin, cirsimaritin, and pectolinarigenin in CNE, with multiple reaction monitoring analysis confirming their content (4.426, 0.569, and 0.078 mg/g, respectively). Interestingly, all identified compounds increased TNF-α production in RAW264.7 cells without displaying cytotoxicity. Our findings demonstrate that CNE and pectolinarin potentially enhance innate immunity and restore attenuated immunity by activating the nuclear factor-kappa B signaling pathway.